2009
DOI: 10.1538/expanim.58.403
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Alteration in Hippocampal Neurogenesis Correlates with Learning Performance of Macaque Monkeys

Abstract: Newborn neurons are continuously produced in the hippocampus, which may be involved in several cognitive functions, including learning and memory, throughout life. However, both hippocampus-dependent cognitive functions and the level of adult neurogenesis are gradually attenuated as aging progresses. Few studies have explored the relationship between adult neurogenesis and cognitive functions, especially in primates. In this study, we evaluated learning performance and hippocampal neurogenesis utilizing young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 23 publications
(27 reference statements)
5
47
0
2
Order By: Relevance
“…One month after testing their spatial memory abilities in the water maze, it was found that animals with preserved spatial reference memory, that is, aged-unimpaired rats, showed a higher level of cell proliferation and a higher number of new neurons in comparison to rats with spatial memory impairments, that is, aged-impaired rats (Drapeau et al 2003). This correlative relation was confirmed in rats (Driscoll et al 2006), monkeys (Aizawa et al 2009), and, recently, in humans (Coras et al 2010), reinforcing its physiological significance.…”
Section: Correlationsmentioning
confidence: 79%
“…One month after testing their spatial memory abilities in the water maze, it was found that animals with preserved spatial reference memory, that is, aged-unimpaired rats, showed a higher level of cell proliferation and a higher number of new neurons in comparison to rats with spatial memory impairments, that is, aged-impaired rats (Drapeau et al 2003). This correlative relation was confirmed in rats (Driscoll et al 2006), monkeys (Aizawa et al 2009), and, recently, in humans (Coras et al 2010), reinforcing its physiological significance.…”
Section: Correlationsmentioning
confidence: 79%
“…Although there is no overt age-related loss of neurons in the monkey hippocampus, aged monkeys have fewer proliferating cells in the DG subgranular zone, and these cells also exhibit shorter and irregularly oriented dendritic processes (Aizawa et al 2009(Aizawa et al , 2011. These studies suggest that aged monkeys have attenuated hippocampal neurogenesis (Aizawa et al 2009), possibly due to decreased survival of immature neurons (Aizawa et al 2011).…”
Section: Neurons Of the Hippocampus And Related Cortical Regionsmentioning
confidence: 79%
“…These studies suggest that aged monkeys have attenuated hippocampal neurogenesis (Aizawa et al 2009), possibly due to decreased survival of immature neurons (Aizawa et al 2011). Additionally, preliminary findings point to a potential relationship between the number of proliferating cells in the subgranular zone and learning capacity (Aizawa et al 2009). …”
Section: Neurons Of the Hippocampus And Related Cortical Regionsmentioning
confidence: 92%
“…These phenomena occur in these neurogenic regions of the adult brain in rodents as well as in primates, including humans (Eriksson et al, 1998;Gould et al, 1999;Kornack andRakic, 1999, 2001;Spalding et al, 2013). Hip-pocampal neurogenesis is associated with learning and memory (Imayoshi et al, 2008;Aizawa et al, 2009). Altered neurogenesis in the hippocampus has been implicated in major depression (Cameron and Gould, 1994;Czéh et al, 2001;Malberg and Duman, 2003;Snyder et al, 2011).…”
Section: Introductionmentioning
confidence: 99%